Adsorption of chromium from aqueous solution using treated oil palm fibre - Naimah Ibrahim; Mohamed Hasnain Isa; Ragunathan Santiagoo (Universiti Teknologi Mara (UiTM), 2008)
Organized by Universiti Teknologi Mara (UiTM) Cawangan Pulau Pinang, 8th - 9th December 2006 at UiTM Cawangan Pulau Pinang.